DEDIKASI DAN LOYALITAS PENGABDIAN PELATIH YANG BERKARAKTER UNTUK INDONESIA - Banar Budiono (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
TNI General LBMoerdani sentence fragment : II The Best of All My ability Dedicate To Nusa And Nations II, inspired my personal self to invite all the people of Indonesia and especially the Faculty of Sport UNY ( which I am proud alma mater ) to jointly download DEDICATION - right ourselves each to the nation and the unitary Republic of Indonesia.As creative beings sporting , Sportive and adaptive let us pause for a moment to think critically seek a solution in the face of global change and the proliferation of sports science and technology . Being innovative is not easy without any deliberate effort and full consciousness . To be creative and innovative then we need to have characteristics such as: l.Self confidence , attitude 2.Questioning, 3.Curiousity, 4.Thirst for knowledge , 5.Knowledge , 6.Practice experience , 7 Capability for social interaction and a sense of humor , 8.Problem orientation , 9.Sensitivity to posibilities , 10. Persistence ll.Determination , 12.Ability to simplify 13.Sensibility, 14.Manualdextreity.All can be realized immediately, after the father 's mother out of the room . So we hereby speech , may be a material reflection for all of us , especially the men and women sports, and alumni of the institution . Thus, the hope of this nation , to have a sportsman, athlete , coach , teacher penjas , sports coaches , sports managers and institutional professional sports in accordance with the mandate of Law No. Sports System . 3 of 2005, can actually be realized. Keywords : Dedication , Loyalty , Coach , and character.